The potential to improve air quality by increasing the use of deep geothermal energy - Hajto, Marek; Kaczmarczyk, Michał (Geology, geophysics & environment, 2022)
Increasing the use of geothermal energy may be one of the tools bringing us closer to achieving the European Commission’s objective of reducing greenhouse gas emissions by 55% by 2030. Air quality improvement plays a strategic role in achieving sustainable energy development. Both European and national legislation in this field is particularly comprehensive and effective, establishing rules for monitoring and preventing air pollution in order to avoid adverse effects on human health and the environment. Unfortunately, the effective air pollutions monitoring network currently in place in Poland, with 156 monitoring stations, mainly concerns agglomerations and cities with over 100,000 inhabitants. The lack of information on the state of pollution in smaller towns is a significant limitation in terms of research aimed at assessing the effects of corrective measures taken, such as the possible transformation of district heating systems based on RES, including the use of deep geothermal energy. This paper proposes some solutions which allow the effective estimation of air conditions in locations not covered by environmental monitoring, in the context of the potential to develop geothermal resources in the rich geothermal province of Central Poland.